Identification of a high-affinity glycine betaine transport system in Staphylococcus aureus. - Bae, J H (1993)
Staphylococcus aureus accumulates proline and glycine betaine when cells are grown at low water activity. In the present study, we have identified a high-affinity glycine betaine transport system in this bacterium. Optimal activity for this transport system was measured in the presence of high NaCl concentrations, but transport activity was not stimulated by high concentrations of other solutes.